ASSESSMENT OF ENVIRONMENTAL PROJECTS - Олех, Татьяна Мефодиевна; Руденко, Сергей Васильевич; Гогунский, Виктор Дмитриевич (Eastern-European Journal of Enterprise Technologies, 2013)
The environmental assessment of the project is Oone of the most important parts of project management. Due to the increasing relevance of the state environmental policy, wide-scale implemented is the projects environmental assessment. The environmental assessment should ensure the creation of conditions when different variances of their preparatory stage do provide environmental requirements compliance, and the impact of proposed activities onto the environment is identified at the early stage of project preparation and can be taken into account during its development and implementation. Of particular importance are the social problems, environmental and economic analysis, and analysis of the projects environmental risks. The article describes the goals and objectives of the environmental assessment.The role and place of environmental assessment are shown as structural identifiers at the investment cycle. Formation the selection criteria and indicators of priority project principles are considered in detail. The structure of the organization of works on the evaluation of the project, including the phasing and integrated documentation required for environmental assessment providing and financial solutions taking are represented. The purpose of the environmental assessment is to collect, process and report all the relevant project data. The article contains examples of compiling the «Summary table of the project prioritization» and «Report on the environmental screening».The results of this article can be used on the stage of the project environmental assessment phase.